Safety and Efficacy of a Novel “Hybrid Closure” Technique in Large-Bore Arteriotomies - Amponsah, Michael K.; Tayal, Rajiv; Khakwani, Zain; Sinclair, Michael; Wasty, Najam (International Journal of Angiology, 2017)
The “preclose” technique employing two Perclose (P) devices is well established for large-bore artery (LBA) hemostasis. Occasionally, only one Perclose deploys successfully during the initial preclose because of arterial calcification necessitating the use of the crossover balloon technique to achieve hemostasis at the LBA. We sought to determine if the combined use of one Perclose and either one Angioseal or one Mynx vascular closure device (VCD) is a safe alternative closure technique large-bore arteriotomy closure.In total, 40 patients underwent high-risk percutaneous coronary intervention (HRPCI) with Impella support, of whom 38 had common femoral artery (CFA) arteriotomies and 2 underwent percutaneous axillary arteriotomy (AA). Prior to Impella insertion, one Perclose device was predeployed. At the end of HRPCI, Impella was removed and a 0.035″ wire was inserted through the Impella sheath. This sheath was then withdrawn over the wire, and partially deployed Perclose was fully deployed. A 6-Fr sheath was advanced over a 0.035″ wire into the CFA or AA, achieving hemostasis and reducing the LBA to a 6-Fr size. The 6-Fr arteriotomy was closed with a 6-Fr Mynx or Angioseal VCD. Patients were followed at day 1 and day 30.Hybrid closure was successful in 38 of 40 cases. In one case of Mynx balloon rupture, hemostasis was achieved with heparin reversal and manual compression. In the case of Perclose failure, crossover balloon tamponade at arteriotomy site and external manual compression achieved hemostasis. Patients were free of complications at day 1 and day 30.Hybrid closure with one Perclose and either one Mynx or one Angioseal VCD is safe and effective for LBA closure.
Keywords: cardiac catheterization; vascular closure device; high-risk PCI